Advancing Evidence-Based Public Health Policy: How Core Component Thinking Can Illuminate the Nature of Public Health Policy? - Fadhel Nasser Mohammed Alasmakh et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Public health policy is critical for improving population health, but its effectiveness depends on identifying and implementing key elements that drive success. Core component thinking—a framework derived from implementation science—offers a structured approach to dissecting public health policies by distinguishing essential components from adaptable features. This review explores how core component thinking can enhance evidence-based public health policymaking by clarifying mechanisms of impact, improving scalability, and ensuring contextual adaptability. Drawing on examples from tobacco control, sugar-sweetened beverage taxation, and COVID-19 mitigation, we argue that this approach can bridge the gap between research and policy. Challenges, including political feasibility and data limitations, are discussed, along with recommendations for future research and practice. Keywords: public health policy, evidence-based policy, core components, implementation science, health interventions Received Date: February 25, 2024 Accepted Date: March 12, 2024 Published Date: April 17, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/387 DOI: https://doi.org/10.5281/zenodo.15716431